(untitled) (REMUNOM, 2025)
Polychrus acutirostris (Spix, 1825) (Sauria: Polychrotidae) is an arboreal lizard from the Brazilian Cerrado that employs opportunistic predation strategies on insects, including bees and wasps. This study describes the feeding behavior of the species in a rural area near a highway in Andradina, São Paulo. During diurnal observations, an individual was recorded foraging on a flowering Eucalyptus tree, directly capturing five pollinating insects, including three Apis mellifera and one Polybia cf. sericea. The lizard used its tail to extend its reach, occasionally supporting itself on its hind limbs, and maintained continuous predatory behavior without showing signs of discomfort when attacking stinging insects. Prey capture appears to be influenced by factors such as food availability, nutritional value, and opportunity, highlighting the behavioral flexibility of P. acutirostris. The species adjusts its diet according to the presence of insects in the environment, maximizing foraging success. Direct predation observations on flowers are rare, and this represents the first documented record of behavioral strategies involving the predation of Apis mellifera and Polybia cf. sericea by P. acutirostris. These findings contribute to the understanding of predator–prey interactions in Cerrado ecosystems and underscore the importance of opportunistic records in elucidating previously understudied aspects of the feeding ecology of arboreal lizards.